A Human, Organization, and Technology Perspective on Patients' Experiences of a Chat-Based and Automated Medical History-Taking Service in Primary Health Care: Interview Study Among Primary Care Patients - Evalill Nilsson; Annette Sverker; Preben Bendtsen; Ann Catrine Eldh (JMIR Publications, 2021)
BackgroundThe use of e-visits in health care is progressing rapidly worldwide. To date, studies on the advantages and disadvantages of e-consultations in the form of chat services for all inquiries in primary care have focused on the perspective of health care professionals (HCPs) rather than those of end users (patients). ObjectiveThis study aims to explore patients' experiences using a chat-based and automated medical history-taking service in regular, tax-based, not-for-profit primary care in Sweden. MethodsOverall, 25 individual interviews were conducted with patients in the catchment areas of 5 primary care centers (PCCs) in Sweden that tested a chat-based and automated medical history-taking service for all types of patient inquiries. The semistructured interviews were transcribed verbatim before content analysis using inductive and deductive strategies, the latter including an unconstrained matrix of human, organization, and technology perspectives. ResultsThe service provided an easily managed way for patients to make written contact with HCPs, which was considered beneficial for some patients and issues but less suitable for others (acute or more complex cases). The automated medical history-taking service was perceived as having potential but still derived from what HCPs need to know and how they address and communicate health and health care issues. Technical skills were not considered as necessary for a mobile phone chat as for handling a computer; however, patients still expressed concern for people with less digital literacy. The opportunity to take one's time and reflect on one's situation before answering questions from the HCPs was found to reduce stress and prevent errors, and patients speculated that it might be the same for the HCPs on the other end of the system. Patients appreciated the ability to have a conversation from almost anywhere, even from places not suitable for telephone calls. The asynchronicity of the chat service allowed the patients to take more control of the conversation and initiate a chat at any time at their own convenience; however, it could also lead to lengthy conversations where a single issue in the worst cases could take days to close. The opportunity to upload photographs made some visits to the PCC redundant, which would otherwise have been necessary if the ordinary telephone service had been used, saving patients both time and money. ConclusionsPatients generally had a positive attitude toward e-visits in primary care and were generally pleased with the prospects of the digital tool tested, somewhat more with the actual chat than with the automated history-taking system preceding the chat. Although patients expect their PCC to offer a range of different means of communication, the human, organization, and technology analysis revealed a need for more extensive (end) user experience design in the further development of the chat service.